2022
DOI: 10.3390/cryst12070953
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methane Pre-Reforming Percentage and Flow Arrangement on the Distribution of Temperature and Thermal Stress in Solid Oxide Fuel Cell

Abstract: To obtain detailed information on the temperature field and thermal stress field inside the solid oxide fuel cell (SOFC) fueled with partially pre-reformed methane. A three-dimensional geometric and mathematical model of the SOFC is implemented by using the finite element method in the commercial software COMSOL Multiphysics®. The coupling characteristics were analyzed for electrode chemical reaction, multi-component mass transfer, and heat transfer process under typical operating conditions, which was further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The heat is generated by the charged-species (oxygen ions and electrons) transport, activation polarization, and exothermic electrochemical reaction. The heat generated is predominantly conducted through metallic ribs owing to their large thermal conductivity [ 27 ], and the heat is in turn transported to the inlet gases carried by them. It is also noted that there is a significant temperature difference between the cell and the outside environment, which also causes some of the heat to be radiated from the outer walls through electromagnetic waves [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The heat is generated by the charged-species (oxygen ions and electrons) transport, activation polarization, and exothermic electrochemical reaction. The heat generated is predominantly conducted through metallic ribs owing to their large thermal conductivity [ 27 ], and the heat is in turn transported to the inlet gases carried by them. It is also noted that there is a significant temperature difference between the cell and the outside environment, which also causes some of the heat to be radiated from the outer walls through electromagnetic waves [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The charge transfer mainly includes the transfer of electrons in the conductor and the transfer of oxygen ions in the electrolyte material. The ion and electron conservation can be expressed as [ 27 ]: where σ ion,eff and σ elec,eff are the ionic conductivity and electrical conductivity, respectively, i is the current density, and A ve is the specific surface area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they found that higher inlet temperatures not only increased power output but also improved the uniformity of the cell temperature distribution. Cai et al 16 constructed a contact thermomechanical model considering the effective mechanical properties of composite electrode materials using finite element software. They investigated the impact of inlet fuel types (hydrogen, methanol syngas) and flow arrangements (co-flow, counter-flow) on performance indicators of the cell, such as high-temperature zones, current density, and maximum thermal stress.…”
mentioning
confidence: 99%